Effects of long term iodized table salt consumption on serum T3, T4 and TSH in an iodine deficient area of Bangladesh - Parveen, S; Latif, SA; Kamal, MM; Uddin, MM (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jan;16(1):57-60.The abstract of this article is available on the PubMed website